2021
DOI: 10.1016/j.clnesp.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Precision and accuracy of bioelectrical impedance analysis devices in supine versus standing position with or without retractable handle in Caucasian subjects

Abstract: Background & aims: Bioelectrical impedance analysis (BIA) could be facilitated in subjects who are able to stand by using scales without (BIA std4 ) or with a retractable handle (BIA std8 ), provided that they are as precise as BIA devices commonly used in the supine position in the hospital setting (BIA sup ). This observational prospective cross-sectional study aimed to compare the precision and accuracy of BIA std4 , BIA std8 and BIA sup in a Caucasian population. Methods: Fat mass percentage (FM%) was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Among the several methods available, the usage of BIA in this study instead of DXA, which presents a widely available non-invasive instrument [ 3 , 54 ] and has also been suggested as a reference standard [ 54 ], might have overestimated the muscle mass [ 55 ]. One study has even suggested the possibility of standing multi-frequency BIA (the same as used in this study) overestimating the fat mass percentage in women with higher BMIs in comparison to both the supine BIA and DXA methods [ 56 ]. With respect to the different forms of BIA, good inter-unit precision and no differences between the standing and supine BIA were reported [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the several methods available, the usage of BIA in this study instead of DXA, which presents a widely available non-invasive instrument [ 3 , 54 ] and has also been suggested as a reference standard [ 54 ], might have overestimated the muscle mass [ 55 ]. One study has even suggested the possibility of standing multi-frequency BIA (the same as used in this study) overestimating the fat mass percentage in women with higher BMIs in comparison to both the supine BIA and DXA methods [ 56 ]. With respect to the different forms of BIA, good inter-unit precision and no differences between the standing and supine BIA were reported [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has even suggested the possibility of standing multi-frequency BIA (the same as used in this study) overestimating the fat mass percentage in women with higher BMIs in comparison to both the supine BIA and DXA methods [ 56 ]. With respect to the different forms of BIA, good inter-unit precision and no differences between the standing and supine BIA were reported [ 56 , 57 ]. However, BIA as a technique was shown to have an acceptable accuracy [ 58 , 59 ], was recommended for use in research [ 3 ], presented a high degree of correlation with the DXA approach [ 20 , 60 ] and magnetic resonance imaging (MRI) [ 61 ] in the muscle mass assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their transfer to other levels should be made according to individual characteristics and necessities. Lastly, recent studies have observed a lack of agreement in BIA measurements between supine and standing positions, even in raw bioelectrical parameters [ 61 , 62 ]. Therefore, our reference values should not be compared with those obtained with supine bioimpedance analyzers.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the patient’s body during the test is of great importance. Some researchers have emphasized the advantage of lying over standing [ 18 , 19 , 20 ] due to the better equalization of fluid levels, and thus more reliable research results, especially in relation to the hydrated spaces of the body. In addition, using the BIA apparatus adapted to the supine position, we were also able to estimate selected body composition parameters in seriously ill people who are immobilized in bed [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the main problem is the comparison of the data obtained with a given measuring tool with the results of other researchers who also use the BIA method, but with a different starting position of the patient. There are single research results analyzing different measuring devices in the same study group [ 18 , 23 , 24 ]. An additional problem is the technological differences that have been reported to potentially correspond to the disagreement between devices, where different frequencies are used in different devices [ 25 ].…”
Section: Introductionmentioning
confidence: 99%